Worker Participation in Canada: Some Lessons from the Past - Fricke, John (Relations industrielles / Industrial Relations, 1988)
The author examines how the participation scheme proposed by the Royal Commission on the Economie Union and Development Prospects for Canada (Macdonald Commission) can be made viable and enduring.